AMONG THE NEIGHBORS AND EMPIRES: THE ROLE OF BELIZE IN REGIONAL GEOPOLITICS (Tzintzun, Revista de Estudios Históricos, 2016)
The purpose of his article is to analyze the role of Belize in regional geopolitics along the major stagesof its history, with special emphasis on the twentieth century. First, we study the decades from the early1963, when belize attained self-government; then we examined the period between 1963 and 1981,which includes key issues such as the struggle for independence and the Central American crisis. Italso analyzes the years of independence to the present. Throughout the article problems such as the roleof Belize in the regional context, the relationship between the domestic and political aspects of Belize tothe regional countries are analyzed, the strategies of the major external actors (Mexico, Great Britainand the United States), and conflicts of the Government of Belize with Central American countries,particularly with Guatemala. Likewise, discussions addressed the independence of Belize ininternational forums, the role of Mexico in connection with the defence of self-determination of thepeople of Belize and the positions of Central American governments closer to Washington. Finally, wereview the conflict of territorial division of the government of Belize with its neighbors, Guatemala andMexico.
Keywords: Geopolitics; independence; exterior policy; territorial division; Belize; Mexico; Guatemala; Central America